Geopolitical relations and regional restructuring: the case of the Kumaon Himalaya, India - Gerwin, Martin; Bergmann, Christoph (ERDKUNDE, 2012)
While the formation and regulation of international borders have long been on the agenda of geographical and social science research, the actions of populations residing in state-peripheries have received inadequate attention so far. Our case study focuses on the so-called ‘Bhotiyas’ in North India’s Kumaon Himalaya. The Bhotiyas consist of several valley communities who were formerly involved in trans-Himalayan trade. Their ethnic identities and livelihoods remain closely linked to the area of the Sino-Indian border, which was sealed as a result of the war between the two countries in 1962. We contend that these borderlanders are not passive victims of geopolitically induced interventions, but rather active participants in the restructuring of their contested live worlds. Based on the assumption that geopolitical realities are forged across a variety of scale-levels, we analyze shifting livelihoods in terms of both a specific socio-cultural context and broader webs of relations to which people have access or from which they are excluded. This offers new insight into highland-lowland interactions of mountain systems and brings the utilization of natural resources more strongly to the fore of borderland studies.